Global research status and hotspot analysis of meniscal root tears based on the WOS database - Wang, Yifan; Huang, Chen; Qi, Yansong; Bao, Huricha; Xu, Yongsheng (Frontiers in Surgery, 2022)
Background: Meniscal root tears are one of the common diseases in the field of orthopedics and sports medicine today and are mostly caused by sports injuries. Purpose: This study aims to identify and evaluate the global trends, hotspots and frontiers in meniscal root tear research using bibliometric analysis. Methods: A bibliometric analysis of research findings related to meniscal root tears over the past three decades was performed. CiteSpace and VOSviewer were used to conduct document co-citation and cluster analyses on the collected data. The research was conducted based on the following factors: country and institution distribution, chronological distribution, source journal analysis, keyword co-occurrence analysis, and reference co-citation analysis. Results: A total of 626 research articles on meniscal root tears in English published from 1989-2021 were obtained. There was a significant upward trend in the total number of scientific publications over the past decades, especially in 2015-2020. The most productive countries, institutions, journals and authors are the USA, STEADMAN PHILIPPON, KNEE SURGERY SPORTS TRAUMATOLOGY ARTHROSCOPY, and LAPRADE RF. North America and East Asia made outstanding contributions to the research on meniscal root tears, but cooperation and exchanges between countries and institutions were not close enough. A total of 9 clusters were obtained from the citation analysis, and 8 clusters were obtained from the keyword analysis. The main keywords that ranked first were posterior root tear, medial meniscus, menisci tibial, and ACL reconstruction, and these clusters combined with the corresponding emergence reflected the current status of research at different times. Conclusion: Research in this field over the past 32 years has gone through a phase of exploration in the understanding of the anatomy of the meniscal root and the diagnosis of this disease and a phase of development with in-depth biomechanical studies and improved and innovative surgical techniques. The current research focuses on the innovation of meniscal root tear repair techniques, the long-term efficacy of surgery, the variability in the efficacy of different surgical techniques, and surgical strategies for combined injuries. There will be more breakthroughs in surgical techniques, surgical equipment and surgical materials to resolve meniscal root tears.